2019
DOI: 10.1142/s1363919620500607
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entrepreneurial Leadership and Configuring Core Innovation Capabilities to Enhance Innovation Performance in a Disruptive Environment

Abstract: Digital disruption leads to high-level risk in innovation management that will impact established firms in disrupted industries. This study investigates the key variables to enhance innovation performance (IP) in a disruptive environment by applying strategic entrepreneurship framework from [Hitt, MA, DG Sirmon, RD Ireland and CA Trahms (2011). Strategic entrepreneurship: Creating value for individuals, organizations, and society. Academic of Management Executive, 25(5), 57–75]. This study sampled the managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 70 publications
4
21
0
1
Order By: Relevance
“…So the hypotheses H1, H2, and H3 were accepted. It was in line with Utoyo et al (2019), which found out that the entrepreneurial mindset, entrepreneurial culture, and entrepreneurial leadership affected strategic resource management in two large telecommunications and banking companies in Indonesia. The organizational resource variable had the highest t-statistic value indicating that the organizational resource variable influenced the resource orchestration variable more strongly than the environmental-factor and individual resource variables.…”
Section: Evaluation Of Inner Modelsupporting
confidence: 66%
See 1 more Smart Citation
“…So the hypotheses H1, H2, and H3 were accepted. It was in line with Utoyo et al (2019), which found out that the entrepreneurial mindset, entrepreneurial culture, and entrepreneurial leadership affected strategic resource management in two large telecommunications and banking companies in Indonesia. The organizational resource variable had the highest t-statistic value indicating that the organizational resource variable influenced the resource orchestration variable more strongly than the environmental-factor and individual resource variables.…”
Section: Evaluation Of Inner Modelsupporting
confidence: 66%
“…Entrepreneurial leadership is the ability to influence others in achieving goals, looking for opportunities, managing resources strategically, and create an entrepreneurial climate so that it becomes an advantage to maintain competitiveness (Fontana and Musa, 2017;Anju and Mathew, 2017). Entrepreneurial culture refers to an organizational culture committed to fostering and supporting the importance of simultaneous opportunity-seeking and profit-seeking behavior (Utoyo et al 2019). However, the indicator of entrepreneurs' commitment to develop, improve their employees' knowledge, skills, and managerial abilities had the lowest average.…”
Section: Descriptive Analysis Of Strategic Entrepreneurship In Bogor mentioning
confidence: 99%
“…Furthermore, Lawson & Samson (2001) stated that the stronger a company's innovation capability was, the more effective its innovation performance is. Previous studies show that innovation capability affects innovation performance (Prajogo & Ahmed, 2006;Sözbilir, 2018;Utoyo et al, 2020;Yeşil et al, 2013). Thus, there is an exchange of ideas, information, experiences, and skills among MSME individuals (the owners, managers, employees, competitors) in the knowledge sharing process.…”
Section: Introductionmentioning
confidence: 95%
“…Firstly, entrepreneurship in general and entrepreneurial leadership, in particular, have been considered as ways of thinking and lifestyle rather than merely establishing an organisation (Utoyo et al 2020). In this sense, entrepreneurial characteristics and approaches can be applied to improve all aspects of education and schooling, specifically school leadership through influencing individuals' behaviours and their task achievements (Mukesh et al 2020).…”
Section: Entrepreneurial Leadershipmentioning
confidence: 99%